The abc-problem for Gabor systems - Dai, Xin-Rong, 1971-; Sun, Qiyu, 1966- (Memoirs of the American Mathematical Society, 2016)
A longstanding problem in Gabor theory is to identify time-frequency shifting lattices a\mathbb{Z}× b\mathbb{Z} and ideal window functions χ_I on intervals I of length c such that \{e^{-2π i n bt} χ_I(t- m a):\ (m, n)\in \mathbb{Z}× \mathbb{Z}\} are Gabor frames for the space of all square-integrable functions on the real line. In this paper, the authors create a time-domain approach for Gabor frames, introduce novel techniques involving invariant sets of non-contractive and non-measure-preserving transformations on the line, and provide a complete answer to the above abc-pro.